Secure deduplication and integrity audit system based on convergent encryption for cloud storage - Xiao-yong GUO; An-min FU; Bo-yu KUANG; Wei-jia DING (Tongxin xuebao)
Cloud storage applications quickly become the best choice of the personal user and enterprise storage with its convenience,scalability and other advantages,secure deduplication and integrity auditing are key issues for cloud storage.At first,convergent key encapsulation/decoupling algorithm based on blind signature was set up,which could securely store key and enable it to deduplicate.Besides,a BLS signature algorithm based on convergence key was provided and use TTP to store public key and proxy audit which enables signature and pubic key deduplication and reduces client storage and computing overhead.Finally,cloud-based secure deduplicaion and integrity audit system was designed and implemented.It offered user with data privacy protection,deduplication authentication,audit authentication services and lowered client and cloud computation overhead.